2020
DOI: 10.35912/amor.v1i1.299
|View full text |Cite
|
Sign up to set email alerts
|

Elements influencing the success of Human Resource Information System

Abstract: Purpose: Due to the upgrade of technology, it has swapped the methods of controlling human beings in companies. In this context, finding the elements influencing the success of the HRIS in ABC manufacturing (Pvt) Ltd was the current research motive. Research methodology: The study design was deductive and quantitative. Moreover, primary data with Scale questionnaire was utilized for data gathering. 30 executives were selected in ABC manufacturing (Pvt) Ltd have directly dealt with the HRI System. Further, dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
1
0
Order By: Relevance
“…Srivastava et al (2021) comprehend HRIS as "a suite of software, database and cloud computing which provide an all-encompassing solution for managing every aspect of a workforce." Dissanayake and Nandasena (2020) explains HRIS as an interrelated system that collects, stores and interprets HR-related data in a firm. Bali (2019) maintains that HRIS is a system that is used to collect, record, store, analyse and retrieve, the data related to an organisation's HR.…”
Section: Definitions Of Human Resource Managementmentioning
confidence: 99%
“…Srivastava et al (2021) comprehend HRIS as "a suite of software, database and cloud computing which provide an all-encompassing solution for managing every aspect of a workforce." Dissanayake and Nandasena (2020) explains HRIS as an interrelated system that collects, stores and interprets HR-related data in a firm. Bali (2019) maintains that HRIS is a system that is used to collect, record, store, analyse and retrieve, the data related to an organisation's HR.…”
Section: Definitions Of Human Resource Managementmentioning
confidence: 99%
“…They indicated that the cost of hiring someone online is estimated to be about one-twentieth of the total estimated cost for offline recruitment. Online or electronic jobs can use the Internet to advertise vacancies, provide information about jobs and organisations, and communicate via emails between job seekers and employers ( (Dissanayake & Nandasena, 2019); (Bans-Akutey, 2022)). Job seekers can virtually apply for jobs by applying online through e-mailing application forms and resumes to employers or human resource managers of business organisations.…”
Section: E-recruitmentmentioning
confidence: 99%
“…HRMIS is one of the many integrated services in ERP [5]. Companies in the telecommunication, banking, and manufacturing industries mostly use HRMIS [6], however while implementing and adopting HRMIS, almost every organization faces challenges such as employee resistance to use, technological incompatibility, and incurring huge costs on installation and training of employees [7,8].…”
Section: Introductionmentioning
confidence: 99%